If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -3(2x + 9) = 15 Reorder the terms: 12 + -3(9 + 2x) = 15 12 + (9 * -3 + 2x * -3) = 15 12 + (-27 + -6x) = 15 Combine like terms: 12 + -27 = -15 -15 + -6x = 15 Solving -15 + -6x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -6x = 15 + 15 Combine like terms: -15 + 15 = 0 0 + -6x = 15 + 15 -6x = 15 + 15 Combine like terms: 15 + 15 = 30 -6x = 30 Divide each side by '-6'. x = -5 Simplifying x = -5
| 3(6z-1)-4(z+2)=5(z+1) | | 4d+3=8 | | 7x+4x=12 | | -9x-1=71 | | 7x+4+=12 | | 217-5x=40x+22 | | 10-7x=127-28x | | 10-7x=127-18x | | 114-5x=2x+26 | | -8x-5=19 | | 5x^2+3x=3 | | 5y-2x=10 | | 0.04(x-0.2)=-0.03(2x+0.6) | | .167x^2-.333x-1=0 | | 9x+5=2x+33 | | 25-x^2= | | 8x-2x+18=0 | | (1+7i)+(9-1)=0 | | 0.3(c+5)=0.4(1-2c) | | r^2+5=0 | | r^2+1=0 | | x/(x-3)+3=5x/(3-x) | | 2(x-0.2)=3x-1.4 | | 3R+5-R= | | 10x^2-30x=0 | | (2x-1)+(x-11)+x+40=360 | | 4x+19=26-3x+8x | | 2x+4-20x=10 | | -3m+12=-48 | | 9+3x=39-12x | | 3x+5=1-x | | -2=-2(k+19) |